2008
DOI: 10.1016/j.ejheart.2008.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adipose derived stromal cells is associated with functional improvement in a rat model of chronic myocardial infarction

Abstract: Aims: To determine the effect of transplantation of undifferentiated and cardiac pre-differentiated adipose stem cells compared with bone marrow mononuclear cells (BM-MNC) in a chronic model of myocardial infarction. Methods: Ninety-five Sprague-Dawley rats underwent left coronary artery ligation and after 1 month received by direct intramyocardial injection either adipose derived stem cells (ADSC), cardiomyogenic cells (AD-CMG) or BM-MNC from enhanced-Green Fluorescent Protein (eGFP) mice. The control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
117
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(131 citation statements)
references
References 44 publications
12
117
1
Order By: Relevance
“…One study reported that ADMSCs show properties similar to macrophages in wounds. 16 In another study, it was shown that pre-adipocytes can develop macrophage-like phagocytic characteristics. 32 In our study, although the data are preliminary and it only confers the in vitro results, it has been shown, for the first time, that visceral and cutaneous leishmaniasis-causing parasite types can infect ADMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that ADMSCs show properties similar to macrophages in wounds. 16 In another study, it was shown that pre-adipocytes can develop macrophage-like phagocytic characteristics. 32 In our study, although the data are preliminary and it only confers the in vitro results, it has been shown, for the first time, that visceral and cutaneous leishmaniasis-causing parasite types can infect ADMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although increased numbers of reports have been published on the effectiveness of ADMSCs in animal models and several phase III clinical trials, similar disease transmission risks can also be applicable in stem cell transplantations using adipose tissue and its cellular derivatives. 15 Although the phagocytic property of ADMSCs has been reported in one study, 16 to our knowledge, there have not been any studies that report the interaction between ADMSCs and Leishmania parasites. For this reason, in this study, the interaction between ADMSCs and the different types of Leishmania parasites have been investigated in vitro .…”
mentioning
confidence: 93%
“…In animal models of infarction these cells have been proven capable of improving ventricular function [11,12].…”
Section: Bone Marrow Cellsmentioning
confidence: 99%
“…Indeed, very recent studies have shown the therapeutic efficacy of ADSCs, which were isolated (and cultured) by different methods, in animal MI models. 9,[16][17][18] However, precise mechanistic insights of the favorable effect of ADSCs on cardiac functional recovery following MI have never been shown in the previous reports. We therefore tested the hypothesis that hMADCs had a favorable effect on acute MI exhibiting its capability of differentiation into vascular cells and cardiomyocytes and other biological activities in ischemic myocardium.…”
mentioning
confidence: 99%
“…On the other hand, tissues such as cord blood, 4 placenta, 5 skeletal muscle, 6 skin, 7 and adipose tissue-derived resident stem cells 8,9 have also been shown to have regenerative capacity in certain diseases, including cardiovascular disease animal models. Among the various sources of tissue-derived stem cells, adipose tissue-derived stem cells (ADSCs) are one of the promising candidates as a tool for cell-based regenerative medicine, and the usage of ADSCs are not remote from clinical field because of its feasibility for collecting sufficient number of cells with the methodological simpleness.…”
mentioning
confidence: 99%